Residential complexes and the risk of the “city-as-compound” regime - Kovalev, Nickolay; Meisner, Tatiana; Barkova, Eleonora (project baikal, 2026)
The widespread replication of residential complexes increases the risk that everyday life becomes enclosed within private perimeters, weakening the city’s public framework. The study identifies the mechanism through which an “archipelago of residential complexes” forms and delineates the features of a “residential-complex regime.” The paper formulates design and regulatory principles – permeability and connectivity, genuine publicness, functional-temporal mixing, ecological resilience of the external urban edge, and fairness of access. Institutionalising these principles reduces urban fragmentation and the displacement of externalities.